Community Attitudes Towards Biosecurity in Animal Based Tourism - Devi Yunita Sari; Fransiskus Trisakti Haryadi; Michael Haryadi Wibowo; Siti Andarwarti; Yustina Yuni Suranindiyah (Faculty of Animal Science, Universitas Brawijaya, 2023)
Biosecurity is an effort to protect livestock and reduce the risk of spreading diseases that have a negative impact on livestock. This study aims to measure the attitude of the public towards the application of biosecurity. We surveyed 100 tourists who visited Sato Loka, which is an animal-based tourist object, using a questionnaire that has been tested for validity and reliability. The data were analyzed using descriptive analysis and scoring. The results show that the travelers' attitudes for the cognitive, affective, and conative indicators were 92.9%, 92%, and 91%, respectively. These indicators are interrelated; cognitive indicators are related to knowledge, which is closely related to changes in one's attitude. The majority of tourists who visit are young tourists (17-25 years old). Young tourists have good cognitive abilities because they are able to absorb various information quickly so that it will influence their actions towards something. The study concludes that most tourists who visit Sato Loka have a very positive attitude towards the application of biosecurity, but there is still an attitude that needs to be enhanced further regarding the use of special footwear when entering the wildlife area in order to create a safe and comfortable tourist attraction, both for tourists and animal.